A genealogy of the food bank: Historicising the rise of food charity in the UK. Issue 3 (6th March 2022) - Williams, Andrew; May, Jon
Abstract: It is widely supposed that food banks and key aspects of the UK's wider food banking system – referral networks, eligibility tests, food vouchers, corporate sponsorship, and the close entanglement of food charity with local and national government – are new to the UK, either imported from North America or emerging ex nihilio with the Trussell Trust in the early 2000s. Drawing on local and national newspaper archives and data from Companies House, the Charity Commission, and internet archiving website the WayBack Machine, we present a genealogy that challenges these origins and situates UK food banking in a set of historically contingent practices, alliances, and struggles, many of which are nowadays forgotten. Contributing to work on policy mobilities in the voluntary sector, we pay particular attention to the development of the UK's contemporary food banking system through the movement of ideas and practices between different organisations (for example, between food banks, corporate food retailers, and US tech companies) and different charitable fields (including overseas aid and homelessness), between the charitable sector and the state, and between different places both within and outside the UK. The resulting genealogy not only extends, and reframes, the history of British food banking – including claims as to the recent institutionalisation of food banks in a neoliberal state welfare apparatus – but works to disrupt the rationalities and 'regime(s) of acceptability' that underpin and maintain the modus operandi of many current‐day food banks. Abstract : This paper presents a genealogical account that challenges the typical origin stories told about food banks in the UK. It situates their emergence within a set of historically contingent practices, alliances, and struggles, many of which are nowadays forgotten.